2018
DOI: 10.1513/annalsats.201707-568kv
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease. A Biomarker and a Potential Therapy

Abstract: This article assesses developments in cardiorespiratory medicine since the Nobel Prize in Physiology or Medicine was awarded in 1956 for advancements in the study of cardiorespiratory disease. In chronic obstructive pulmonary disease, advances were accelerated by the discovery of a genetically determined cause for pulmonary emphysema in the genetic abnormality alpha-1 antitrypsin deficiency. This causes a deficiency of the inhibitor of neutrophil elastase, which results in increased degradation of lung elastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…39, 40, 42 Later, human studies confirmed similar findings. 15, 41, 42 Stone et al extensively explored levels of D/I in relation to presence of COPD, or with smoking status. 43 They found higher excretion of D/I in urine of COPD patients, and in smokers without presence of COPD compared to healthy lifetime nonsmokers, suggesting smoking and the presence of COPD to be independently associated with elevated urinary D/I levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39, 40, 42 Later, human studies confirmed similar findings. 15, 41, 42 Stone et al extensively explored levels of D/I in relation to presence of COPD, or with smoking status. 43 They found higher excretion of D/I in urine of COPD patients, and in smokers without presence of COPD compared to healthy lifetime nonsmokers, suggesting smoking and the presence of COPD to be independently associated with elevated urinary D/I levels.…”
Section: Discussionmentioning
confidence: 99%
“…12 Lung elastin is a recognized target for injury in COPD, and systemic levels of D/I, which are specific for elastin degradation, are elevated in COPD as well as in those without COPD but with acute exposure to tobacco smoke, direct or secondhand. [13][14][15] However, it is unclear whether past remote exposure to SHS in those without a diagnosis of COPD is also associated with continued lung injury, elastin degradation, and elevated levels of D/I.…”
Section: Introductionmentioning
confidence: 99%